ANALISIS SAMPUL BUKU TEMA PERKEMBANGAN TEKNOLOGI: ANALISIS SAMPUL BUKU TEMA PERKEMBANGAN TEKNOLOGI - yurike bala; Rahmat Olii (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Textbooks are textbooks in certain fields, which are learning tools that will be developed according to the curriculum in relevant learning policies. One of the textbooks in a certain field is an integrated thematic book with the title of the 7th theme book "technology development" which is used in grade 3 elementary schools. This book is a book that has been compiled and prepared for the implementation of the 2013 curriculum. One of the learning approaches that must be used in the implementation of the 2013 curriculum, namely the scientific approach (scientific approach). A very real change in the 2013 curriculum is the approach used and the application of authentic assessment. In this book, students will learn how technology develops according to the times. This is with the aim that students understand the function of technology that is able to facilitate human work, this book is also accompanied by interesting pictures so that it can attract the attention of students to read it. This thematic book is a guide book that makes it easier for students to be active in learning. Textbooks that contain thematic learning characteristics so as to optimize the learning process. This book is suitable for students at the elementary school level. Besides that, the function of textbooks is also as a facility for independent learning activities, both about the substance and about the presentation. The use of textbooks is part of the book culture, which is one of the signs of an advanced society. Viewed from the learning process, textbooks have an important role.